Regulators of Slc4 bicarbonate transporter activity - Thornell, Ian M.; Bevensee, Mark O. (Frontiers in Physiology, 2015)
The Slc4 family of transporters is comprised of anion exchangers (AE1-4), Na-coupled bicarbonate transporters (NCBTs) including electrogenic Na/bicarbonate cotransporters (NBCe1 and NBCe2), electroneutral Na/bicarbonate cotransporters (NBCn1 and NBCn2), and the electroneutral Na-driven Cl-bicarbonate exchanger (NDCBE), as well as a borate transporter (BTR1). These transporters regulate intracellular pH (pHi) and contribute to steady-state pHi, but are also involved in other physiological processes including CO2 carriage by red blood cells and solute secretion/reabsorption across epithelia. Acid-base transporters function as either acid extruders or acid loaders, with the Slc4 proteins moving HCO3– either into or out of cells. According to results from both molecular and functional studies, multiple Slc4 proteins and/or associated splice variants with similar expected effects on pHi are often found in the same tissue or cell. Such apparent redundancy is likely to be physiologically important. In addition to regulating pHi, a HCO3– transporter contributes to a cell’s ability to fine tune the intracellular regulation of the cotransported/exchanged ion(s) (e.g., Na+ or Cl–). In addition, functionally similar transporters or splice variants with different regulatory profiles will optimize pH physiology and solute transport under various conditions or within subcellular domains. Such optimization will depend on activated signaling pathways and transporter expression profiles. In this review, we will summarize and discuss both classical and more recently identified regulators of the Slc4 proteins. Some of these regulators include traditional second messengers, lipids, binding proteins, autoregulatory domains, and less conventional regulators. The material presented will provide insight into the diversity and physiological significance of multiple members within the Slc4 gene family.